Culturally Responsive Pedagogy for Teachers of Color. Issue 3 (3rd July 2017) - Gist, Conra D.
ABSTRACT: This study utilizes the conceptual framework of culturally responsive pedagogy and theoretical suppositions about the culturally responsive teacher educator to examine the learning experiences of teacher candidates of color. Findings from the case study of a teacher educator's and teacher candidates' of color teaching and learning experiences in a semester-long course revealed the following: (a) The teacher educator's culturally responsive content was characterized by resistance, revelation, and support and (b) culturally responsive teacher educator pedagogy involved instructional approaches of modeling change and building community. Implications for culturally responsive pedagogies in the teacher education classroom and professional development are explored.